The Association Between Physical Activity and Subclinical Atherosclerosis: The Multi-Ethnic Study of Atherosclerosis - Bertoni, Alain G. (Oxford University Press, 2009)
Prior reports regarding the association between physical activity and subclinical cardiovascular disease have not been consistent. The authors assessed physical activity and walking pace via questionnaire among 6,482 US adults aged 45–84 years without prior clinical cardiovascular disease participating in the Multi-Ethnic Study of Atherosclerosis from 2000 to 2002. Ankle-brachial index (ABI), coronary artery calcification, and internal and common carotid intima-media thickness (IMT) were measured. Metabolic equivalent-hours/week of physical activity were calculated. These data were analyzed by using multivariable linear or relative prevalence regression in gender-specific strata. After adjustment for age, race/ethnicity, clinic site, education, income, and smoking (model 1), increasing total, moderate + vigorous, and intentional-exercise physical activity were not associated with IMT or coronary artery calcification in either gender. These factors were associated with increased ABI (P < 0.05) in women only. Walking pace was associated favorably with common carotid IMT, ABI, and coronary artery calcification in men and with common carotid IMT and ABI in women (all P < 0.05) after adjustment for model 1 variables. These associations were attenuated and, for common carotid IMT, no longer significant when lipids, hypertension, diabetes, and body mass index were added to the model. These data suggest that walking pace is associated with less subclinical atherosclerosis; these associations may be mediated by cardiovascular disease risk factors.